Quranic Recitation Guidance In Improving The Quality Of Education At Raudhatul Athfal Al-Aliy Kendal Waru Timur Pamekasan - Wahyudi, Ahmad; Mukarromah, Kamilatul; Kusaini, Nasrul Hadi Bin (STAI Publisistik Thawalib Jakarta, 2023)
Reciting the Qur'an nurtures students' spiritual, moral, and cognitive development, builds character, enhances worship, and fosters a connection with Allah from an early age. The purpose of this study is to explore and describe Qur'anic recitation guidance and its impact on quality at Raudhatul Athfal Al-Aliy Pamekasan. This research uses a qualitative method with a case study approach. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data condensation, presentation, and conclusion drawing. Data validity techniques include credibility and confirmability tests. The findings of the study are as follows: (1) Qur'anic recitation guidance: (a) Pre-guidance: preparation of recitation tools, teaching method planning, and student motivation. (b) Guidance process: quizzes, transportation games, and recitation sessions. (c) Post-guidance: student performance assessment, journaling, and awarding recognition. (2) The impact of the Qur'anic guidance: (a) On the school: enhancement of learning facilities. (b) On teachers: improved teaching creativity. (c) On students: increased learning enthusiasm. (d) On parents: better understanding of students' progress. Conclusion: Qur'anic recitation guidance provides a positive impact on students, teachers, parents, and the school.